Late Ordovician And Early Silurian Graptolites, Cape Phillips Formation, Canadian Arctic Archipelago - Melchin, Michael Jerome (Scholarship@Western, 1987)
Ashgill and Llandovery graptolites have been collected from eleven sections in the Cape Phillips Formation of the Canadian Arctic Archipelago: from Melville, Bathurst, Truro, Cornwallis, Devon and Ellesmere islands.;A total of 179 graptolite species and a further 25 subspecies have been identified including 19 new species, 11 new subspecies, 2 new genera and 1 new subfamily. Their stratigraphic distribution has allowed the recognition of 13 graptolite zones. The two in the Ashgill are the fastigatus and pacificus zones while the acuminatus, atavus, acinaces, cyphus, curtus, convolutus, minor, turriculatus, crispus, griestoniensis and sakmaricus zones are found in the Llandovery. These zones can be correlated with graptolite sequences worldwide.;The Canadian Arctic faunas show strong affinities with those of Siberia and China as well as with the northern Canadian Cordillera although many European elements are also present. It may be possible to recognize a circum-equatorial faunal province in Northern Canada, Siberia and China based on the occurrence of several distinctive forms including Agetograptus and 'Paramonoclimacis" in the Middle Llandovery and Cyrtograptus (especially C. sakmaricus) in the Upper Llandovery.;Study of the uncompressed diplograptids has revealed that several main proximal development patterns can be recognized among these Llandovery forms and these patterns may be used to arrive at a more phylogenetically realistic classification scheme as has been recently accomplished for the Ordovician graptoloids. This new scheme shows that only Hedrograptus proceeds from middle Ordovician times into the Llandovery and gives rise to the major Early Silurian graptolite radiation. This took place after the other Ordovician forms were entirely decimated by the Late Ordovician extinction event.;The evidence, from what is presently known of the proximal development patterns and their stratigraphic ranges, indicates that Atavograptus, the first monograptid genus, arose from either Akidograptus or ...